Ekosistem Terumbu Karang Pulau Arborek Raja Ampat, Papua Barat - Dian Sutono HS; Robert Perangin-angin; Mustasim Mustasim (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2020)
Raja Ampat Regency is known to have tropical marine biodiversity which is estimated to be the richest in the world at the moment. Potential coral reef resources owned by Raja Ampat Regency, are part of the